Provisions of Legal Aid as a Form of Protection for Child Victims of Rape - Zainurohmah, Zainurohmah; Febriansyah, Andhika; Andini, Marcelia Puspa; Saputro, Muhammad Eko; Mukhoyyaroh, Vina Durrotul; Rohman, Bintang Nur (The Digest: Journal of Jurisprudence and Legisprudence, 2023)
Indonesia as a state of law guarantees the human rights of its citizens, one of which is the right to equal treatment before the law. Legal aid is one of the state's efforts to fulfill this right for the poor. This research aims to examine the provision of legal aid in Indonesia, which departs from the case study of child rape that occurred in Banyumas. This research uses normative juridical method with statutory approach and conceptual approach. The results of this study show that the state has accommodated the need for legal aid as regulated in Law Number 16 of 2011 concerning Legal Aid. However, those who need legal aid are not only poor people but also children who are victims of rape. The provision of legal aid to child victims of rape is a form of state responsibility in providing legal protection to children so that the rights that children should get as stated in the Child Protection Law can actually be realized, not limited to being stated in the law.